2014
DOI: 10.5539/hes.v4n4p24
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Approaches to Learning and Perceptions of the Teaching-Learning Environment During Bachelor Level Studies and Their Relation to Study Success

Abstract: The aim of the present study is to explore changes both in approaches to learning as well as in students' experiences of the teaching-learning environment and how these changes are related to each other during their Bachelor studies by using a longitudinal data set. The aim is further to explore how students' approaches to learning and their perceptions of the teaching-learning environment relate to study success. Participants comprised of 103 students at the Faculty of Biological and Environmental Sciences wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 38 publications
5
53
1
Order By: Relevance
“…Students react and respond in line with their experience of the learning environment and what they perceive is required of them by the learning institution (Asikainen et al, 2014;Marton and Bowden, 1999). Dominant teaching cultures tend to profile students to become either proactive or reactive learners.…”
Section: Learning Approachmentioning
confidence: 90%
“…Students react and respond in line with their experience of the learning environment and what they perceive is required of them by the learning institution (Asikainen et al, 2014;Marton and Bowden, 1999). Dominant teaching cultures tend to profile students to become either proactive or reactive learners.…”
Section: Learning Approachmentioning
confidence: 90%
“…Further, variability in approaches to learning has mostly been explored using two measurement points (e.g. Asikainen, Parpala, Lindblom-Ylänne, Vanthournout, & Coertjens, 2014;Vanthournout, Coertjens, Gijbels, Donche, & Van Petegem, 2013), or at most four points (Vanthournout, 2011). HLM can utilise information from multiple measurement occasions and account for both individual and group level effects.…”
Section: Hierarchical Linear Modeling In Exploring Variability Versusmentioning
confidence: 99%
“…Moreover, by using HLM as an analysis method, we may be able to shed light on seemingly paradoxical previous findings where analyses based on the same variables on the within-student level and the between-student level provided seemingly contradictory results. Asikainen et al (2014) analysed changes in students' approaches to learning and perceptions of the TLE from the first to the third study year, and the way that these changes were related to each other. They found that an increase in students' perceptions that teaching supported their understanding was associated with an increase in students' deep approach.…”
Section: Hierarchical Linear Modeling In Exploring Variability Versusmentioning
confidence: 99%
“…HowULearn has its basis in the 'Experiences of Teaching and Learning' research inventory (Entwistle, 2009). The main aim has been to develop a survey that could also act as a base for the university's feedback system and HowULearn has been widely used for evidence-based, quality enhancement purposes across the multidisciplinary University of Helsinki (Parpala et al, 2010;Ruohoniemi et al, 2010;Haarala-Muhonen et al, 2011;Rytkönen et al, 2012;Parpala et al, 2013;Asikainen et al, 2014). To systematically use the HowULearn questionnaire at the University of Helsinki, an online software programme was developed in 2012.…”
Section: Howulearn As a Quality Toolmentioning
confidence: 99%